Syrian Issue in the Discourses of Political Leaders - ÖZCAN, ÖMER FARUK; DEVRAN, YUSUF (MARMARA UNIV, FAC COMMUNICATION, 2016)
Syrian conflict as a part of social movements called as Arab Spring has been turned into a civil war. As a result of this Turkey has come to face with the biggest refugee crisis of its entire history. Thus political parties have used different discourses on Syrian conflict and refugee crisis according to new social, economical and political conditions. In this paper political discourses used by Turkish political leaders between 2011-2015 are examined in the context of their politics for Syrian conflict and refugees. The main goal of this work is to contribute to a better contemplation on the Syrian conflict and refugee crisis by ascertaining political parties' approaches.
Keywords: Syrian Conflict; Turkey; Refugees; Domestic Policy; Political Discourse; Political Parties; Critical Discourse Analysis